Labour movement in Argentina since 1945 : The limits of trade union reformism - Atzeni, Maurizio (2009)
Events at the end of World War II were pivotal for the future of the Argentine labour movement. The military government that took power in 1943, headed by Colonel Juan Domingo Perón, was intent on renewing the process of industrialisation initiated in the 1930s and at the same time halting the spread of communism among the working class. Perón was able to build upon his friendly relations with trade union leaders, creating a durable alliance that would shape the contours of the labour movement and labour relations for decades. Industrialisation in the 1930s had greatly expanded the working class and the trade unions. The 1930s had also created widespread working-class discontent, and with the end of the war approaching, Perón and the military foresaw the coming of a dangerous period of revolutionary turmoil. Through his office of the Secretaría de Trabajo y Previsión, Perón shaped policies to stymie communism through both repression and concessions to appease workers’ political and economic concerns. This ambiguous and reformist set of policies gradually became a grand political project, in which trade unions were to play an integral, two-faceted role as partners in industrial expansion and the backbone of an emergent national political movement.